Management of sowing date of rainy-season crops for sustainable crop yield under dryland condition - Nirval, B G; Chavan, A A; Shinde, J S; Gore, S B (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1983-84 to 1992-93 to study the performance of important rainfed crops sown on different dates under different rainfall patterns. The dry sowing on 15 June of important rainfed crops proved advantageous. viz sorghum [Sorghum bicolor (L) Moench] Rs 10 346/ha. upland cotton (Gossypium hirsutum L.) Rs 9 846/ha, pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz] Â Rs 4 112/ha, sunflower (Hehanthus annuus L.) Rs 6 905/ha, castor (Ricinus communis L.) Rs 5 235/ha, pigeonpea [Cajanus cajan (L.) Millsp.] Rs 9 992/ha, groundnut (Arachis hypogaea L.) Rs 10 811/ha and sesame (Sesamum indicum L.) Rs 5 498/ha. The next-best period was sowing immediately after commencement of rains in normal, above-normal and below-normal rainfall situations. The sowing of crops like castor could be extended up to 30 July under normal and above-normal conditions, whereas that of pigeon pea and pearl millet could be extended up to 30 June in all the rainfall situations without much reduction in their yields and total monetary returns/ha. Most of the rainfed crops gave good performance when sown on 15 June or immediately after rainfall. The crops like sorghum, upland cotton, groundnut and sesame when sown after 30 Juno under all the rainfall conditions gave much less yield and monetary return.